Ways to Ensure Transparency in the Contest of Accelerating Economic Growth in Uzbekistan (Eurasian Scientific Herald, 2022)
The article analyzes approaches to the implementation of the state budget policy in the context of accelerating economic growth. The authors structure the academic discussion about long-term economic growth and its short-term fluctuations and come to the conclusion that in the current situation in Uzbekistan, fiscal policy measures that smooth out fluctuations in economic activity are limited, and there are no opportunities to increase public spending in the medium and long term. Therefore, it is necessary to change the structure of expenditures and at the same time qualitatively transform budgetary institutions in order to create prerequisites for long-term economic growth, and also presents facts and analysis of how to ensure budget transparency based on the same budgetary reforms